OP0071 Risk of Cancer, Serious Lung Infections and Death with Biologics: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials (RCTS). (23rd January 2014) - Singh, J. A.; Wells, G.; Christensen, R.; Ghogomu, E.; Macdonald, J.; Maxwell, L.; Tarp, S.; Buchbinder, R.; Tugwell, P.; ,
Abstract : Background: Biologics are commonly used for the treatment of rheumatoid arthritis (RA) and other inflammatory disorders. The efficacy of biologics is well known, however, less is know about harms, especially how various biologics compare to each other in this respect. Objectives: Our objective was to compare the risk of cancer, serious infections and mortality with the use of biologics using network meta-analysis (NMA). Methods: We used a previously published highly sensitive search strategy (1 ) to identify randomized controlled trials (RCTs) of nine biologics approved for the treatment of RA at the time (abatacept, adalimumab, anakinra, certolizumab pegol, etanercept, golimumab, infliximab, rituximab, tocilizumab). We included the use of these biologics for any indication including but not limited to RA (except HIV/AIDS). We performed mixed-effects logistic regression of trials using standard approved doses of biologics using an arm-based, random-effects model within an empirical Bayes framework and applied a Poisson distribution as the default option. Odds ratios (OR) and 95% confidence intervals (CI) are presented. Results: Thirty-three RCTs with 11, 980 patients were available for the cancer NMA. The overall OR of cancer with all biologics combined was 0.97 (95% CI, 0.64-1.46), compared to control/placebo. There were no significant differences in the odds of cancer with abatacept, adalimumab, certolizumab, etanercept, golimuab, infliximab or rituximab, compared to placebo/control. Anakinra was associated with significantly lower odds of cancer at 0.17 (95% CI, 0.03 to 0.74) compared to control/placebo. Forty-one RCTs with 12, 846 patients were available for the serious lung infections NMA. The overall OR of serious lung infections was significantly higher for all biologics combined at 1.64 (95% CI, 1.07-2.52), compared to control/placebo. There were no significant differences in the odds of serious lung infections with abatacept, adalimumab, anakinra, certolizumab, etanercept, golimumab, rituximab or tocilizumab, compared to placebo/control. Infliximab was associated with a significantly higher OR of serious lung infections at 7.9 (95% CI, 2.2 to 39.6) compared to control/placebo. Fifty-eight RCTs with 19, 852 patients provided data for the mortality NMA. The overall OR of death for all biologics combined was 1.3 (95% CI, 0.88-1.93), compared to control/placebo. There were no significant differences in the odds of death with abatacept, adalimumab, anakinra, certolizumab pegol, golimumab, infliximab, rituximab or tocilizumab, compared to placebo/control. Conclusions: Biologics were associated with a higher risk of serious lung infections, but not cancer or death. More data from RCTs, open-label extension studies and registry studies are needed to draw firm conclusions about rare harms of biologics, such as death and cancer. References: Singh JA, Wells GA, Christensen R, Tanjong Ghogomu E, Maxwell L, Macdonald JK, et al. Adverse effects of biologics: a network meta-analysis and Cochrane overview. Cochrane Database Syst Rev. 2011;2:CD008794. Epub 2011/02/18. Acknowledgements: None Disclosure of Interest: J. Singh Grant/research support from: takeda, Savient, Consultant for: takeda, Savient, allergan, Ardea, Regeneron, Novartis, G. Wells: None Declared, R. Christensen: None Declared, E. Ghogomu: None Declared, J. Macdonald: None Declared, L. Maxwell: None Declared, S. Tarp: None Declared, R. Buchbinder: None Declared, P. Tugwell: None Declared